2021
DOI: 10.1021/acs.energyfuels.0c04290
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and Growth of Gas Hydrates in Emulsions of Water in Asphaltene-Containing Oils

Abstract: Asphaltenes in crude oils may affect hydrate formation in water–oil emulsions, complicating flow assurance and hydrate management in subsea oil–gas multiphase pipelines. In this study, the effects of asphaltenes on hydrate nucleation and growth in water-in-oil emulsions were investigated. It was found that the presence of asphaltenes inhibited hydrate nucleation. The inhibiting effect was enhanced with the increase in asphaltene content from 0 to 0.15 wt % and then was lowered with further increase in asphalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Other factors such as the solubility state of heavy fractions play an important role in affecting hydrate formation. As the solubility of the heavier fraction in the oil phase decreases, it could promote the hydrate plugging tendency. ,, This happens due to the flocculated asphaltene molecules, which act as nucleation sites for hydrates. The addition of a surface-active agent lowers the interfacial tension between the hydrocarbon and water and enhances the contact between the two liquid phases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other factors such as the solubility state of heavy fractions play an important role in affecting hydrate formation. As the solubility of the heavier fraction in the oil phase decreases, it could promote the hydrate plugging tendency. ,, This happens due to the flocculated asphaltene molecules, which act as nucleation sites for hydrates. The addition of a surface-active agent lowers the interfacial tension between the hydrocarbon and water and enhances the contact between the two liquid phases.…”
Section: Resultsmentioning
confidence: 99%
“…38 Some studies have observed that a decrease in solubility of the heavier fraction in the oil could promote the hydrate plugging tendency. 40,43,44 Thus, the inhibition effect has also been observed to be lowered with an increase in asphaltene content. Crude oil is a complex mixture of hydrocarbons, which can be fractionated based on molecular weight and polarity.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…This result was attributed to the hydrate particle diameter and the amount of formed hydrates. For the emulsions with the same water cut, the lower hydrate particle diameter would enlarge the surface area of the hydrate and further increase the dissociation rate. …”
Section: Results and Discussionmentioning
confidence: 99%